Impact of advanced endoscopy training on colonoscopy quality and efficiency - Takashi Watanabe; Tatsuro Murano; Hiroaki Ikematsu; Kensuke Shinmura; Masashi Wakabayashi; Nobuhisa Minakata; Sasabe Maasa; Tomohiro Mitsui; Hiroki Yamashita; Atsushi Inaba; Hironori Sunakawa; Keiichiro Nakajo; et al. (DEN Open)
Abstract Objectives Few reports have detailed improvements in the quality of colonoscopies with continuous training post‐fellowship completion. We examined the changes in colonoscopy performance among trainees during our advanced endoscopy training program. Methods Screening or surveillance colonoscopies performed by 11 trainees who participated in our 3‐year advanced endoscopy training program between April 2015 and March 2020 were retrospectively analyzed. Quality and efficiency metrics of colonoscopies were evaluated annually. Results Altogether, 297, 385, and 438 colonoscopies were enrolled in the first, second, and third training years, respectively. The mean insertion times were 8.6, 7.6, and 6.9 min in the first, second, and third training years, respectively, with significant improvement from the first to second year (p = 0.03) and from the first to third year (p < 0.01). The adenoma detection rate, proximal adenoma detection rate, and mean number of adenomas per patient exhibited a tendency to improve annually; however, the difference was not significant. Polypectomy efficiency was 10.5%, 11.2%, and 13.0%, with significant improvements from the first to third year (p < 0.01) and from the second to third year (p = 0.02). Insertion time and polypectomy efficiency showed significant improvements, especially among trainees experienced with <500 colonoscopies. Conclusions Through our advanced endoscopy training program, there has been an improvement in the quality and efficiency of colonoscopy for trainees who have completed their fellowships, particularly those with <500 colonoscopies.